Effect of antioxidants after post-space irrigation on the adhesive interface of glass fiber post cementation - Cândido, Beatriz Dansini [UNESP]; Manzoli, Tatiane Miranda [UNESP]; Zaniboni, Joissi Ferrari [UNESP]; Besegato, João Felipe; Godoy, Eduardo Fernández; Kuga, Milton Carlos [UNESP]; Dantas, Andréa Abi Rached [UNESP] (Wiley, 2023)
Objective: This study evaluated the effects of antioxidants, 10% sodium ascorbate (SA) or 20% alpha-tocopherol (AT), after post-space irrigation with 2.5% sodium hypochlorite +17% EDTA (SH) or 1% peracetic acid (PA) on the adhesive interface after glass fiber post cementation. Materials and Methods: Sixty bovine roots were endodontically treated. After preparation, the post-space was irrigated with SH or PA followed or not by the use of antioxidants (SA or AT) (n = 10). Push-out bond strength test, failure mode, and dentin penetrability analysis using confocal laser microscope were performed in the cervical, middle, and apical thirds. Data from bond strength and dentinal penetrability were evaluated by one-way ANOVA and Tukey post hoc test (p < 0.05). Results: SH showed the lowest bond strength regardless of the third (p < 0.05). In apical third, mixed failure was the most incident in all groups. Only in the cervical third of the post-space, SH-AT provided the greatest tag extension of the cementation system into dentin (p < 0.05). However, in the middle and apical thirds, SH-AT, SH-SA, and PA-SA provided the largest tag extensions (p < 0.05), but similar to each other (p > 0.05). Conclusions: The use of antioxidants only favored bond strength when SH was used and dentin penetrability of the adhesive and conventional resin cementation, regardless of the solution used to irrigate the post-space. Clinical Significance: The use of antioxidants (10% sodium ascorbate and 20% alpha-tocopherol) after post-space irrigation with sodium hypochlorite appears to increase the bond strength favoring the glass fiber post-cementation.
Keywords: alpha-tocopherol; bond strength; glass fiber post; sodium ascorbate